Workspirit 9 : Why Fusion? : The Future is Fusion. - Rock, Michael; Allais, Lucia (s.l. : vitra, 2004)
Bouroullec, Ronan ; Bouroullec, Erwan ; Citterio, Antonio ; Nguyen, Toan ; Morrison, Jasper ; Aisslinger, Werner ; Meda, Alberto ; Bellini, Mario ; Bellini, Claudio ; Van Severen, Maarten ; Eames, Charles ; Eames, Ray ; Saarinen, Eero ; Panton, Verner ; Prouvé, Jean ; Nelson, George ; Yanagi, Sori
boek